Road freight transport in Mexico: production and employment - Luis David Berrones-Sanz (Universidad Autónoma Metropolitana Unidad Azcapotzalco, 2020)
Road freight transport is the main way of transportation in Mexico; besides it moves the 83.2% of domestic tonnage, it contributes with the 3.96% of the Gross Domestic Product (GDP) and generates 2.73% of employment nationwide. Moreover, its contextualized under a business structure conformed by 152,487 companies, where 97.2% are classified as micro (89.7%) or small companies (16.5%) and that together possess 53% (n=522,221) of the vehicles, that average a seventeen-year-old antiquity. The GDP analysis and the subsector employment show that despite that the number of employed personnel in the road freight transport have a correlation coefficient of 0.99 with Nacional GDP and with the GDP of road freight transport the number of drivers has not increased (AAGR=0.31%) at the same rhythm as the GDP of road freight transport (AAGR=0.97%), and that the National GDP (AAGR=1.36%) of the last years (2008-2013) resulting in an over 80,000 driver scarcity: this despite that this workgroup has relatively higher incomes than the average of workers and in a national context where there is a lack of job opportunities. However, the output elasticity of employment in the last lustrum is 15-19=1.009, and the evidence shows that despite the economic situation of 2020 and the reduction of production there will not be any reduction in the number of drivers in the road freight transportation area (19-20=0.94) and, as a result, it seems that they will not have unemployment risks. Hence, it is interesting to analyze the market, the process and context of drivers employment, as variables which contribute to the explanation between the growth differences of these indicators. Which is why, in this sense, it is remarked the necessity of improving the labor working conditions of drivers, under the premise that it is an investmentand not a cost, given that positive changes will allow to reduce the scarcity, while improving the level of service and competitiveness in the supply chain.